GNSS e dati geografici costituiscono la quinta infrastruttura primaria globale (GEOmedia, 2014)
2014 is the year of the official start of services provided by European Galileo satellite positioning system, and even if a few years late, the expectations for the induction of a rapidly growing market are many, with expected growth more then doubled by 2022.The latest forecasts of the market in GNSS derived from GNSS Market Report released last year by the European GNSS Agency (GSA) suggest a global market that is facing rapid developments even during a global recession like the one we are facing now.